2023
DOI: 10.1200/jco.2023.41.17_suppl.lba3503
|View full text |Cite
|
Sign up to set email alerts
|

Phase III randomized clinical trial comparing the efficacy of neoadjuvant chemotherapy and standard treatment in patients with locally advanced colon cancer: The NeoCol trial.

Abstract: LBA3503 Background: Locally advanced colon cancer presents a therapeutic challenge regarding improving survival and minimizing side effects by optimizing the timing of surgical and systemic treatments. Neoadjuvant chemotherapy is a widely accepted approach in numerous cancers as it aims to eliminate micrometastases and reduce tumor size. Our study aimed to assess the impact of neoadjuvant chemotherapy on locally advanced colon cancer compared to standard initial surgery. Methods: This was a randomized, contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Recent meta‐analyses have indicated that neoadjuvant treatment improves long‐term surgical and oncological outcomes [28, 57, 58]; but the final role of NAC in LACC in the therapeutic guidelines remains unresolved [24, 44, 59–62]. This is the reason why the authors consider this topic worthy of continued research, as revealed by the ongoing FOxTROT2 and FOxTROT3, OPTICAL or NeoCol trials [63–65].…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta‐analyses have indicated that neoadjuvant treatment improves long‐term surgical and oncological outcomes [28, 57, 58]; but the final role of NAC in LACC in the therapeutic guidelines remains unresolved [24, 44, 59–62]. This is the reason why the authors consider this topic worthy of continued research, as revealed by the ongoing FOxTROT2 and FOxTROT3, OPTICAL or NeoCol trials [63–65].…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of the present study, two significant RCTs comparing NAC with upfront surgery in patients with LACC were presented at ASCO 2022 and 2023 Meeting, and were subsequently published in abstract form 33 , 34 . To maintain consistency with the inclusion/exclusion criteria of the present study, these trials were not included in the primary analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The Scandinavian NeoCol trial randomized 250 patients with T3 or T4 and N0-2 disease as assessed on CT scan to 3 cycles of CAPOX or FOLFOX prior to surgery versus standard of care with upfront surgery [ 11 ]. The data have been presented but not published.…”
Section: Neoadjuvant Therapy For Pmmr Laccmentioning
confidence: 99%
“…Several randomized controlled trials of perioperative vs adjuvant-only chemotherapy for LACC have reported results recently [ 9 •, 10 , 11 ]. Neoadjuvant immunotherapy is of great interest for patients with deficient mismatch repair (dMMR) LACC given the remarkable pathologic and clinical responses reported in trials of dMMR LACC and rectal cancer [ 12 ••, 13 15 ].…”
Section: Introductionmentioning
confidence: 99%